Hippocampal Anti-inflammatory Effect of Electroacupuncture at Baihui and Shenting on Cognitive Dysfunction Induced by Systemic Inflammation - CHEN Xiaomei; PANG Lina; WANG Zhifu (康复学报)
ObjectiveTo investigate the hippocampal anti-inflammatory mechanism of electroacupuncture at Baihui and Shenting on cognitive dysfunction induced by Lipopolysaccharide (LPS) intraperitoneal injection.MethodsA total of 45 clean grade adult C57BL/6 male mice (bodyweight 18-22 g) were randomly divided into control group, endotoxic brain injury group (model group) and endotoxic brain injury + electroacupuncture group (EA group). After one week of adaptive feeding, 15 min before LPS injection, the EA group was given 10 Hz electrical stimulation at Baihui and Shenting acupoints, the intensity was 0.5 mA. 15 min after electrical stimulation, the model group and EA group were intraperitoneally injected LPS (1 mg/kg), the control group was given equal volume of solvent injection. 15 min before LPS injection and 24 h after LPS injection, the EA group was given the same electric stimulation for 15 min, and then the “what-where-when” behavioral test was performed to record the memory ability on the time, place and order of objects. After the behavioral experiment, immunofluorescence and ELISA were used to detect the changes of hippocampal Iba-1, TNF-α and serum TNF-α.Results1) Compared with the control group, the learning and memory time related to "what-where-when" in the model group was decreased (P<0.01), and serum TNF-α (3 h after LPS) and hippocampal TNF-α (24 h) were significantly increased (P<0.01); immunofluorescence and ELISA detection showed that hippocampal Iba-1 was significantly increased (P<0.01) in the model group. 2) Compared with the model group, "what" and "when" learning time in the EA group increased (P<0.01); the serum and hippocampal TNF-α were obviously decreased (P<0.01 and P<0.05); hippocampal Iba-1 in the EA group was decreased (P<0.05).ConclusionElectroacupuncture at Baihui and Shenting may improve the cognitive dysfunction caused by systemic inflammation via inhibiting the activation of hippocampal microglia and reducing the release of inflammatory factor TNF-α in the peripheral blood and hippocampal regions.